Leaf characteristics of rice cultivars with a stronger yield response to projected increases in CO2 concentration. Issue 3 (5th November 2020) - Wang, Weilu; He, Jiang; Wang, Zhiqin; Gu, Junfei; Liu, Lijun; Zhang, Weiyang; Ziska, Lewis H.; Zhu, Jianguo
Abstract: Rising levels of atmospheric carbon dioxide (CO2 ) could, potentially, be exploited as a means to increase seed yield and maintain food security, especially for cereal grains. Although there have been multiple cultivar trials indicating that significant yield variation occurs, the basis for these differences has not been entirely elucidated. Here, we focus on two rice cultivars that differed in field trials to their yield sensitivity to elevated CO2 : Yangdao6hao (YD6), and Wuyunjing23 (W23) to assess whether observed yield differences (YD6 > W23) were associated with concurrent changes in leaf‐level characteristics. At ambient levels of CO2, leaf net photosynthesis ( A ) of YD6 was compatible with that of W23. However, at elevated CO2, A was higher for YD6 relative to W23. The stability of leaf Rubisco content, biochemical characteristics ( V c, max, and J max ), nitrogen enzymatic activity, and chlorophyll concentration differed significantly, with greater values observed for YD6 relative to W23 at elevated CO2 . While such results are consistent with other studies, we also demonstrate that a higher ratio of carbon sinks (seed) to carbon sources (leaf), were linked to increases in cytokinins, and slower flag leaf senescence for the YD6 relative to the W23 cultivar at elevated CO2 . While additional data for a broader genetic selection are needed, the current study suggests a link between source/sink carbon assimilation, maintenance of photosynthetic biochemistry, and slower leaf senescence for rice cultivars that show a stronger yield response to projected CO2 levels. This information, in turn, may provide suitable metrics for future CO2 selection among rice cultivars.